A Natural Food Colourant from Dioscorea alata (Dandila) in Sri Lanka: Development, Storage Stability and Bio-active Properties - W.A.E.M.P. Menike; J.W.A. Sajiwanie; R.M.U.S.K. Rathnayaka (Sumatera Medical Journal, 2024)
Background: Though anthocyanins are popular as natural food colourants with additional functional properties, their instability limited their utilization in the industry. Objective: this study aimed to formulate a natural food colourant by the microwave-assisted encapsulation of Dandila (Dioscorea alata) anthocyanins to enhance the storage stability of the pigments in ambient conditions and to study the storage stability and the bio-active properties of the formulated colourant. Methods: This was an in vitro study, the steps were acidified water was used as the solvent to extract the anthocyanins from Dandila yams. The colourant formulation encapsulated with maltodextrin (30 mg/ml) was selected as the best encapsulation treatment for Dandila anthocyanin. Anthocyanin degradation was not significant during the tested 12 months of storage period. Results: Noteworthy values were obtained for Total Phenolic Content and anti-oxidant activity. Among the tested strains in the antimicrobial assay, the natural colourant showed inhibitory activities against Escherichia coli and Streptococcus pneumoniae. Conclusions:  confirm the successful development of a natural colourant rich in bio-active properties from Dandila anthocyanin while ensuring its storage stability in ambient conditions.